Household economic burden of type-2 diabetes and hypertension comorbidity care in urban-poor Ghana: a mixed methods study - Samuel Amon; Moses Aikins; Hassan Haghparast-Bidgoli; Irene Akwo Kretchy; Daniel Kojo Arhinful; Leonard Baatiema; Raphael Baffour Awuah; Vida Asah-Ayeh; Olutobi Adekunle Sanuade; Sandra Boatemaa Kushitor; Sedzro Kojo Mensah; Mawuli Komla Kushitor; et al. (BMC, 2024)
Abstract Background Non-communicable diseases (NCDs) predispose households to exorbitant healthcare expenditures in health systems where there is no access to effective financial protection for healthcare. This study assessed the economic burden associated with the rising burden of type-2 diabetes (T2D) and hypertension comorbidity management, and its implications for healthcare seeking in urban Accra. Methods A convergent parallel mixed-methods study design was used. Quantitative sociodemographic and cost data were collected through survey from a random community-based sample of 120 adults aged 25 years and older and living with comorbid T2D and hypertension in Ga Mashie, Accra, Ghana in November and December 2022. The monthly economic cost of T2D and hypertension comorbidity care was estimated using a descriptive cost-of-illness analysis technique from the perspective of patients. Thirteen focus group discussions (FGDs) were conducted among community members with and without comorbid T2D and hypertension. The FGDs were analysed using deductive and inductive thematic approaches. Findings from the survey and qualitative study were integrated in the discussion. Results Out of a total of 120 respondents who self-reported comorbid T2D and hypertension, 23 (19.2%) provided complete healthcare cost data. The direct cost of managing T2D and hypertension comorbidity constituted almost 94% of the monthly economic cost of care, and the median direct cost of care was US$19.30 (IQR:10.55-118.88). Almost a quarter of the respondents pay for their healthcare through co-payment and insurance jointly, and 42.9% pay out-of-pocket (OOP). Patients with lower socioeconomic status incurred a higher direct cost burden compared to those in the higher socioeconomic bracket. The implications of the high economic burden resulting from self-funding of healthcare were found from the qualitative study to be: 1) poor access to quality healthcare; (2) poor medication adherence; (3) aggravated direct non-medical and indirect cost; and (4) psychosocial support to help cope with the cost burden. Conclusion The economic burden associated with healthcare in instances of comorbid T2D and hypertension can significantly impact household budget and cause financial difficulty or impoverishment. Policies targeted at effectively managing NCDs should focus on strengthening a comprehensive and reliable National Health Insurance Scheme coverage for care of chronic conditions.